DEI VERBUM AND REVELATION - O’Collins, Gerald (Asian Horizons, 2013)
The 1985 Extraordinary Synod of Bishops met in Rome (24 November to 8 December) to celebrate the Second Vatican Council (which had ended twenty years earlier on 8 December 1965), to evaluate the Council’s role in the postconciliar Church, and to develop some principles for the further reception of its teaching. The final report of the synod produced six principles for interpreting the sixteen conciliar texts.